The interdependence of monetary and macroprudential policy under the zero lower bound - Vivien Lewis; Stefania Villa (National Bank of Belgium, 2016)
This paper considers the interdependence of monetary and macroprudential policy in a New Keynesian business cycle model under the zero lower bound constraint. Entrepreneurs borrow in nominal terms from banks and are subject to idiosyncratic default risk. The realized loan return to the bank varies with aggregate risk, such that bank balance sheets are affected by higher-than-expected firm defaults. Monetary and macroprudential policies are given by an interest rate rule and a capital requirement rule, respectively. We first characterize the model's stability properties under different steady state policies. We then analyze the transmission of a risk shock under the zero lower bound and different macroprudential policies. We finally investigate whether these policies are indeed optimal.
Keywords: E44; E52; E58; E61; G28; 330; capital requirement; macroprudential policy; monetary policy; zero lower bound; Geldpolitik; Finanzmarktaufsicht; Kapitalbedarf; Niedrigzinspolitik